The crisis of the peat industry of the Soviet Union in the 1920s - Voeikov, Evgeniy V. (Journal of the Belarusian State University. History, 2023)
The study of the historical experience of the development of fuel resources of Russia and the Soviet Union will always be relevant due to special climatic conditions. Russia has occupied and still occupies the first place in the world in terms of peat reserves. The history of the peat industry of the Soviet Union is a poorly studied topic, the period of the new economic policy has fallen out of the sphere of scientific interests of historians. Meanwhile, both during the Civil War and in the 1930–50s, peat extraction played an important role in solving the fuel problem in Russia and the USSR. The subject of the study is the development of the peat industry both at the all-Union level and at the micro-level of a separate region of the Middle Volga region in the 1920s. The source base was poorly introduced into scientific circulation materials of regional archives, magazineand newspaper publications of the 1920–30s peat specialists. The article shows the process of mass closure of peat farms in the middle of 1920s and the cessation of the annual growth of peat extraction volumes for several years. In some regions of the country, such as in BSSR, there was a slight increase in the production of this type of fuel, but the insignificant scale of use of this fuel did not correspond to the available resources. A little-known aspect of the history of the peat industry in the 1920s is the beginning of the trend of peat farms becoming a centre of cultural education for peasants coming to work. An indicator of the economic efficiency of the peat industry is the fact of its survival in the conditions of termination of state support during the period of the new economic policy. Peat fuel reserves, according to the data of the 1920s, occupied the second place in the Soviet Union after coal, but firewood occupied the second place after coal in terms of volumes of billets during the period of the new economic policy, which threatened the ecological state of forests. The reduction of financing and decentralisation of the peat industry led to the closure of a number of peat farms, a decline in production on the remaining ones and problems of technical equipment. In addition to low production rates, the peat industry crisis also manifested itself in a reduction in surveys of peat deposits, which subsequently negatively affected the development of peat extraction in the 1930s.
Keywords: history of the peat industry; peat mining of the period of the new economic policy; survey of peat deposits